EMQs and MCQs for surgery finals - Kwak, Hye-Chung. (Chichester, West Sussex : Wiley-Blackwell, 2011)
Revise and prepare for surgical finals with a wide range of questions and comprehensive answers that test your knowledge and help you learn EMQs and MCQs for Surgery Finals is a unique study and revision resource for final examination practice covering all surgical sub-specialties. Each section of the book begins with a brief outline of the surgical topic followed by a range of clinically-based questions to test both knowledge and understanding. The final chapter contains a range of clinical cases that guide you through a real-life scenario on core knowledge tested earlier in the book. This is an essential resource for surgical finals preparation and will assist in providing a rapid refresher, testing understanding, indentifying areas of weaknesses and consolidating knowledge. All in all, a real must-have for any student sitting final surgical examinations.--Provided by publisher.
Machine generated contents note: Essential skills in surgery -- 1 Pre-operative assessment -- Head and neck -- 2 Neurosurgery -- Head injury -- Extradural haematoma -- Subdural haematoma -- Subarachnoid haemorrhage -- Cerebrospinal fluid -- Hydrocephalus -- Cauda equine syndrome -- 3 Ear, nose and throat -- Epistaxis -- Earache -- Foreign bodies -- Tonsillitis -- Parotid swelling -- Thyroid swellings -- Thyroid cancer -- Thyroid gland and hyperparathyroidism -- Chest -- 4 Thorax -- Thoracic trauma -- Rib fracture -- Tension pneumothorax -- 5 Breast surgery -- Mastitis -- Fat necrosis -- Benign breast lumps -- Breast cancer -- Abdomen -- 6 Acute abdomen -- Overview -- Necrotizing fasciitis -- Sigmoid volvulus -- Shock -- ATLS -- 7 Foregut -- The oesophagus -- Dysphagia -- GORD -- Barrett's oesophagus -- Malignant oesophageal tumours -- Gastric cancer -- 8 Hepatobiliary disease -- Pancreatic cancer -- Liver abscess -- Benign hepatic tumours -- Hepatocellular carcinoma -- Cholangiocarcinoma -- Acute pancreatitis -- Chronic pancreatitis -- Pancreatic pseudocysts -- Gallstones -- 9 Spleen -- 0 Midgut -- Acute appendicitis -- Small bowel obstruction -- Meckel's diverticulum -- 11 Colorectal -- Diverticular disease -- Colorectal cancer -- Inflammatory bowel disease -- Lower gastrointestinal bleeding -- Haemorrhoids -- Fissure in-ano -- Fistula in-ano --;12 Nutrition in surgical patients -- 13 Abdominal wall -- Inguinal Hernia -- Femoral Hernia -- Umbilical Hernia -- Incisional Hernia -- Pelvis -- 14 Gynaecology -- Ectopic Pregnancy -- Pelvic Inflammatory Disease -- Ovarian cyst -- 15 Urology -- Urinary tract infection -- Renal colic -- The prostate -- Prostate cancer -- Benign prostatic hypertrophy -- Renal cell carcinoma -- Bladder cancer -- Vascular -- 16 Vascular -- Abdominal aortic aneurysm -- Popliteal artery aneurysm -- Carotid artery disease -- Amputations -- Varicose veins -- Diabetic foot -- ; Peripheral vascular disease -- Acutely ischaemic limb -- Orthopaedic -- 17 Orthopaedic -- Brachial plexus injury -- Radial nerve injury -- Ulnar nerve palsy -- Carpal tunnel syndrome -- Shoulder dislocation -- Colles fracture -- Fractured neck of femur -- Osteoarthritis of knee -- Burns and plastics -- 18 Burns and plastics -- Useful procedures -- 19 Useful procedures -- Draining an abscess -- Urinary catheter insertion -- Examining stomas -- 20 Clinical scenarios -- Answers -- Appendix I: commonly used surgical instruments -- Appendix II: normal ranges for blood tests -- Appendix III: orthopaedic examination.
Includes bibliographical references.
Keywords: Surgical Procedures, Operative